Bone mineral density results influencing health-related behaviors in male athletes at risk for osteoporosis - Fitzgerald, L.; Carpenter, C. (Journal of Clinical Densitometry, 2010)
Abstract The purposes of this study were to determine the role of bone mineral density (BMD) and mood in influencing health-related behaviors of serious leisure male athletes (cyclists and triathletes) at risk for osteoporosis. A cross-sectional design evaluated BMD in 18-60-yr-old serious leisure male cyclists by dual-energy X-ray adsorptiometry (DXA). Activity was measured using the International Physical Activity Questionnaire; personality was assessed using the NEO-60; and quality of life using Short-Form Health 12 (SF-12). Participants completed an online survey questionnaire after completing their DXA testing a minimum of 3mo before assessing health-related behaviors and general attitudes toward general health and well-being. Forty-two (61.9%) participants responded to the follow-up questionnaire. Serious leisure male athletes are more likely to initiate significant health-related behavioral changes after learning of their bone density results including calcium supplementation and weight-bearing exercise. Men with low BMD (LBMD) had higher openness subscales on NEO-60 compared with men with normal BMD. SF-12 mental and physical health scores were significantly lower in men with LBMD. Perhaps, the interaction and interplay of genetics, activity and behaviors, and aspects of mental and psychological functions contribute to their reduction in BMD and heightened risk for fracture. Findings from this study suggest that early BMD testing in "serious athletes" has important clinical relevance for their potential risk for osteoporosis in the future.